Reliability of sprint test indices in well-trained cyclists - Coleman, D. A.; Wiles, J. D.; Nunn, M.; Smith, M. F. (International Journal of Sports Medicine, 2005)
The study aim was to assess reliability of repeated laboratory sprint tests in well-trained endurance cyclists. Eleven male cyclists (mean ± standard deviation: 27 ± 6 yr, 1.79 ± 0.04 m, 70.1 ± 3.3 kg) performed a maximal 30-second sprint test on four separate occasions using their own bicycle fitted with an SRM powermeter on a Kingcycle air-braked ergometer. Peak power output (Wpeak), mean power (Wmean) and an index of fatigue (FI) were calculated. Three minutes post sprint, capillarised blood lactate measurements were taken and analysed. No significant differences (p > 0.05) were found between trials for Wpeak, Wmean, FI and blood lactate concentration. Repeatability of Wpeak, Wmean, and fatigue index improved across trials 2 and 3 when compared to trials 1 and 2. The highest CV for these variables was recorded between trials 3 and 4. The CV for Wpeak was 4.5 ± 1.6 %, Wmean 2.4 ± 1.2 %, and FI 17.2 ± 7.1 %. Intraclass reliability coefficients were 0.93 (95 % CI 0.84 - 0.98), 0.94 (95 % CI 0.86 - 0.98) and 0.89 (95 % CI 0.69 - 0.95) respectively. Blood lactate concentration ranged between 5.35 and 14.52 mmol · l-1, with a mean CV of 12.1 ± 4.2 %. The CV for trials 2 and 3 revealed the highest CV for blood lactate concentration (15.1 %). The lowest CV for this variable (10.2 %) was recorded between trials 3 and 4. The intraclass reliability coefficient for blood lactate concentration was 0.79 (95 % CI 0.58 - 0.93). The results of this study indicate that there is no improvement in the reliability of sprint test indices when assessing well-trained, experienced cyclists, riding on their own cycle equipment.